INTERNET OF THINGS, SEJARAH, TEKNOLOGI DAN PENERAPANNYA : REVIEW - Apri Junaidi (Jurnal Ilmiah Teknologi Infomasi Terapan, 2015)
Internet  of  thing  menjadi  sebuah  bidang penelitian  tersendiri  semenjak  berkembangnya teknologi  internet  dan  media  komunikasi  lain, semakin  berkembang  keperluan  manusia  tentang teknologi,  maka  semakin  banyak  penelitian  yang akan  hadir,  internet  of  things  salah  satu   hasil pemikiran para peneliti yang mengoptimasi beberapa alat  seperti  media  sensor,  radio  frequency identification  (RFID),  wireless  sensor  network  serta smart  object  lain  yang  memungkinkan  manusia mudah  berinteraksi  dengan  semua  perlatan  yang terhubung  dengan  jaringan  internet. Dalam  tulisan ini  penulis  memaparkan  tentang  sejarah  internet  of things,  penerapan  serta  teknologi  yang  digunakan, seperti  penggunaan  internet  of  things  pada  bidang medis,  cloud  computing  dan  beberapa  bidang keilmuan  lain.   Ada  beberapa  bahan  referensi yang digunakan  sehingga  penulis  review  ini  bisa dilakukan, untuk  memperkenalkan  teknologi  internet of things. [EN]Internet of thing becomes a field of research since the development  of  Internet  technology  and  other communications media, growing human needs of the technology,  the  more  research  that  will  be  present,internet  of  things  one  result  of  researchers  to optimize  some  of  the  tools  such  as  media  sensor, radio  frequency  identification  (RFID),  wireless sensor  networks  and  other  smart  object  that  allows humans to easily interact with all the equipment that is connected to the Internet network.In this paper the author describes the history of the internet  of  things,  as  well  as  the  application  of  the technologies  used,  such  as  use  of  the  internet  of things  in  the  medical  field,  cloud  computing  and several  scientific  fields.  There  is  some  reference materials are used so that the authors of this review  can  be  done,  to  introduce  the  Internet  of  things technology.